Partial differential equations : theory and completely solved problems - Hillen, Thomas, 1966-; Leonard, I. Ed., 1938-; Van Roessel, Henry, 1956- (Hoboken, N.J. : Wiley, 2012)
"Combining over 28 years of teaching experience, the authors present a PDE text that is accessible to all students--regardless of their background or mathematical sophistication. The book provides over 150 completely worked problems with solutions and commentaries for both linear partial differential equations and boundary value problems with applications in engineering and biology. Topics covered include a classification of PDEs, heat equation, wave equation, Laplace's equation, separation of variables, Fourier series, classical PDEs, Sturm-Liouville problems, special functions, transform methods, and the method of characteristics for first order PDEs"--
Includes bibliographical references and index.
Keywords: Differential equations, Partial; MATHEMATICS / Differential Equations